Answer:
(3,-3)
Explanation:
First you divide 2 out of the first equation and it turns into 5x+y=12.
Then you write one on top of the other so you can add them. It looks like:
5x + y = 12
-5x + y = -18
Then you add them together and the 5x's cancel each other out and you are left with 2y = -6
So then you divide both sides by 2 and get y = -3
Then you plug -3 into the second equation because it is simpler and get -5x - 3 = -18
So then you add three to both sides and get -5x = -15
And finally you divide both sides by -5 and get x=3